Is There an Indigenous Gothic? - Burnham, Michelle (Scholar Commons, 2013)
This essay surveys scholarship on the role of the American Indian within settler gothic fiction, and outlines the later production of gothic literature by Native American writers in both the United States and Canada. While critically engaging with the traditions and conventions of an earlier Euro-American gothic, however, such fiction also employs indigenous sources of gothic sensation, such as traditional stories about the windigo among the northern Algonquin. This essay argues that histories of American gothic can be enlarged and enriched by recognizing such indigenous contributions to the form.